PERBEDAAN DAN PENERAPAN ANTARA KURIKULUM MERDEKA BELAJAR DAN KURIKULUM K13: PERBEDAAN DAN PENERAPAN ANTARA KURIKULUM MERDEKA BELAJAR DAN KURIKULUM K13 - NurAyu Winingsih; Nelmi Hafizah Mokoginta; Muh. Kadhapy (Jurnal Ilmu Pendidikan dan Budaya, 2022)
SMA Negeri 2 Gorontalo was one of the first schools to implement an independent curriculum in Gorontalo district, this school became the first pilot for implementing an independent curriculum. This curriculum is not based on achieving academic mastery scores and is not only identical to subject matter, but all activities designed by schools to develop students' self-capacity are also included in the curriculum. This is different from the K13 curriculum which was previously used by this school, which is more based on the KKN completeness criteria. This research is intended as a goal to reveal the various differences and implementation of the independent curriculum and also the previous curriculum implemented by SMA Negeri 2 Gorontalo. The research method that the author uses is a qualitative method by using data collection techniques; interviews, documentation, and observation. The research conducted by the authors concluded that the curriculum development model currently used by SMA Negeri 2 Gorontalo is an independent curriculum. With various kinds of learning methods that have been used and which will be developed based on the needs of the students themselves. Development of goals with Development of goals from the independent curriculum with goals The curriculum has an important role and also influences all learning activities. Given the importance of the curriculum in learning activities, curriculum development cannot be made and carried out haphazardly without referring to a foundation.